Twelfth night - Dickins, Rosie (Usborne Pub Ltd; UK, 2009)
This is a new title in "Young Reading Series Two", part of the Usborne Young Reading Programme, which is aimed at children whose reading ability and confidence allows them to tackle longer and more complex stories. Shakespeare's classic comedy is retold in this title. When Viola is left shipwrecked on the coast of Illyria, she must disguise herself as a boy for protection. But when she becomes a page for Duke Orsino, things start to get a little complicated. This title is developed in consultation with Alison Kelly, who is a senior lecturer in education and an early reading specialist from Roehampton University.